A Russian Consul in Newcastle upon Tyne: Baron Al'fons Al'fonsovich Geiking (1860–1930) and Anglo-Russian Connections at the Beginning of the Twentieth Century. (3rd July 2014) - Saunders, David
Abstract : Baron Al'fons Al'fonsovich Geiking (Alfons von Heyking, 1860–1930) served as Russian consul in Newcastle upon Tyne in northern England from 1899 to 1908. His many publications included a 688-page book, England, Its State, Social and Economic Structure: Investigations and Observations in Imperial Russian Consular Service (St Petersburg, 1909). The article gives three reasons for the view that his body of work deserves to be brought into the scholarly domain. First, it pointed out the valuable insights that could be supplied by consuls (more valuable, in Geiking's view, than those of diplomats). Second, it drew in large measure on Geiking's first-hand knowledge of Britain's industrial north (whereas many representatives of foreign countries in Britain came to know only London and the surrounding counties). Third, Geiking was writing at a time of change in Anglo-Russian relations, when the two countries, perennially ambivalent about one another, started associating more closely in the wake of the Entente of 1907. Since, after Newcastle, Geiking served for eight years as Russian Consul-General in London, he was a not inconsiderable figure in the web of connections between Britain and Russia at the beginning of the twentieth century.